Contrasting English and other languages through corpora - Janebová, Markéta; Lapshinova-Koltunski, Ekaterina; Martinková, Michaela (Cambridge Scholars Publishing, 2017)
This volume is grounded on the latest research in empirical contrastive language studies, addressing several issues on contrasts between English and other languages. It results from an annual workshop on language contrasts, organised by the International Computer Archive of Modern and Medieval English (ICAME), and covers a wider range of phenomena in phraseology, discourse and pragmatics. As it relies on data from parallel or comparable corpora, it gives valuable insights into cross-linguistic differences between English and other languages, which might otherwise go unnoticed.The book will be useful to experts on language studies and advanced students with an interest in linguistics. It will serve as a catalyst to other researchers interested in the contrastive analysis of the English language. The results of the linguistic analyses described within will be valuable for practical applications in lexicography, language teaching and translation (both human and machine), including translator training.